2007
DOI: 10.2174/092986707779313516
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Agents and Applications to Assess Tumor Angiogenesis In Vivo by Magnetic Resonance Imaging

Abstract: Angiogenesis plays a key role in the development of cancer and is precondition for tumor growth, invasion and spread. Therefore, numerous angiogenesis inhibitors have been developed, of which some show potential to defeat cancer in preclinical and clinical trials. However, response to antiangiogenic treatments is often delayed and marked by high interindividual variability making a closely mashed and efficient observation of the patient necessary. Therefore, surrogate markers which specifically catch early res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 114 publications
0
50
0
Order By: Relevance
“…As positive MR contrast agents (bright on T1), Gd-loaded polymers (e.g. poly-lysine dendrimers, N-(2-hydroxypropyl)methacrylamide (HPMA) -co-polymers)(4) and paramagnetic liposomes (6) as well as very small superparamagentic iron oxide nanoparticles, such as citrate-coated very small superparamagnetic iron oxide nanoparticles (VSOP) (14) were successfully applied in preclinical and/or clinical trials. Unfortunately, none of these agents was finally approved for clinical use.…”
Section: Nanoparticles As Diagnostic Probesmentioning
confidence: 99%
“…As positive MR contrast agents (bright on T1), Gd-loaded polymers (e.g. poly-lysine dendrimers, N-(2-hydroxypropyl)methacrylamide (HPMA) -co-polymers)(4) and paramagnetic liposomes (6) as well as very small superparamagentic iron oxide nanoparticles, such as citrate-coated very small superparamagnetic iron oxide nanoparticles (VSOP) (14) were successfully applied in preclinical and/or clinical trials. Unfortunately, none of these agents was finally approved for clinical use.…”
Section: Nanoparticles As Diagnostic Probesmentioning
confidence: 99%
“…(34)). Hydrophilic PEGylated conjugate (140) was found to possess superior in vivo pharmacokinetics with higher tumor-to-blood, tumor-to-liver, tumor-to-muscle, and tumor-to-lung ratios with respect to more lipophilic counterparts (141) and (142). This demonstrated that the chemical nature of the attached beacon moiety can be rationally tuned to tailor the overall biodistribution profile of the radiotracer.…”
Section: Radionuclide Imagingmentioning
confidence: 98%
“…Optical imaging, in particular fluorescence imaging and magnetic resonance imaging, nicely complements the above mentioned radionuclide-based techniques in "seeing" within the living body and understanding the biological complexities for disease treatment [141]. In the last few years, several research groups have demonstrated the utility of coupling v 3 -directing cyclic RGD peptides to optical-and MRactive molecular beacons for use in noninvasive in vitro, in vivo, and ex vivo imaging of tumor-related angiogenesis.…”
Section: Optical and Magnetic Resonance Imagingmentioning
confidence: 99%
“…Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) is one of the evaluation methods of anti-angiogenic agents, such as anti-VEGF antibody and tyrosine kinase inhibitor, clinically (Morgan et al, 2003;O'Connor et al, 2007) and preclinically (Marzola et al, 2004;Nakamura et al, 2006;Bradley et al, 2009), by calculating pharmacokinetic parameters, including fractional plasma volume (v p ) and the volume transfer constant (K trans ) from the enhancement of tumour signal intensity by gadolinium (Gd) contrast agent (Tozer, 2003;Kiessling et al, 2007). To my knowledge, however, there are no reports to evaluate TbR-I inhibitor by DCE-MRI.…”
mentioning
confidence: 99%